Structural behaviour and parametric study of reinforced embankments on soft clays - José Leitão Borges (2001)
Geotechnical behaviour of a reinforced embankment on soft ground is studied by a numerical model based on the ®nite element method. Special emphasis is given to the stress states (stress levels and pore pressures), displacements, tensile forces in the geosynthetic and overall stability, during and after construction. The in¯uence of some parameters, namely geosynthetic sti ness and viscosity, embankment width and construction sequence, is also analysed. Several conclusions are obtained.